The Human Milk Oligosaccharides 3‐FL, Lacto‐N‐Neotetraose, and LDFT Attenuate Tumor Necrosis Factor‐α Induced Inflammation in Fetal Intestinal Epithelial Cells In Vitro through Shedding or Interacting with Tumor Necrosis Factor Receptor 1. Issue 7 (3rd March 2021) - Cheng, Lianghui; Kong, Chunli; Wang, Wenjia; Groeneveld, Andre; Nauta, Arjen; Groves, Matthew R.; Kiewiet, Mensiena B. G.; de Vos, Paul
Abstract : Scope: Human milk oligosaccharides (hMOs) can attenuate inflammation by modulating intestinal epithelial cells, but the mechanisms of action are not well‐understood. Here, the effects of hMOs on tumor necrosis factor‐α (TNF‐α) induced inflammatory events in gut epithelial cells are studied. Methods and results: The modulatory effects of 2'‐fucosyllactose, 3‐fucosyllactose (3‐FL), 6'‐sialyllactose, lacto‐N‐tetraose, lacto‐N‐neotetraose (LNnT), lactodifucotetraose (LDFT), and lacto‐N‐triaose (LNT2) on immature (FHs 74 Int) and adult (T84) intestinal epithelial cells with or without TNF‐α are determined. Interleukin‐8 (IL‐8) secretion in FHs 74 Int and T84 are quantified to determine hMO induced attenuation of inflammatory events by ELISA. 3‐FL, LNnT, and LDFT significantly attenuate TNF‐α induced inflammation in FHs 74 Int, while LNT2 induces IL‐8 secretion in T84. In addition, microscale thermophoresis assays and ELISA are used to study the possible mechanisms of interaction between effective hMOs and tumor necrosis factor receptor 1 (TNFR1). 3‐FL, LNnT, and LDFT exert TNFR1 ectodomain shedding while LNnT also shows binding affinity to TNFR1 with a Kd of 900 ± 660 nM. Conclusion: The findings indicate that specific hMO types attenuate TNF‐α induced inflammation in fetal gut epithelial cells through TNFR1 in a hMO structure‐dependent fashion suggest possibilities to apply hMOs in management of TNF‐α dependent diseases. Abstract : Human milk oligosaccharides (hMOs) can attenuate inflammation by modulating intestinal epithelial cells, but the mechanisms are not well‐understood. The anti‐inflammatory effects of different hMOs are tested on tumor necrosis factor‐α induced inflammation in immature and mature intestine epithelial cells. This study shows that the anti‐inflammatory effects of hMOs are structure‐dependent and through interference with tumor necrosis factor receptor 1 signaling.